а) 4x² - 4x - 15 < 0
D = b² - 4ac = 16 + 4*4*15 = 16 + 240 = 256
x₁ = (-b + √D) / 2a = (4 + 16) / 8 = 20 / 8 = 2,5
x₂ = (-b - √D) / 2a = (4 - 16) / 8 = -12 / 8 = -1,5
(x - 2,5)(х + 1,5) < 0
{ x < 2,5
{ x < -1,5
ответ: (-1,5; 2,5)
б) x² - 81 > 0
(x - 9)(x + 9) > 0
{ x > -9
{ x > 9
ответ: (-9; 9)
в) x² < 1,7х
x² - 1,7х < 0
х(x - 1,7) < 0
{ x < 0
{ x < 1,7
ответ: (0; 1,7)
г) x( x + 3) - 6 < 3 (x + 1)
x² + 3x - 6 - 3x - 3 < 0
x² - 9 < 0
(x - 3)(x + 3) < 0
{ x < -3
{ x < 3
ответ: (-3; 3)
0.12∗
6
1
=
100
12
∗
6
1
=
6∗100
12∗1
=
1∗100
2∗1
=
50
1
=0.02
2.1*\frac{3}{7}=\frac{21}{10}*\frac{3}{7}=\frac{21*3}{10*7}=\frac{3*3}{10*1}=\frac{9}{10}=0.92.1∗
7
3
=
10
21
∗
7
3
=
10∗7
21∗3
=
10∗1
3∗3
=
10
9
=0.9
3\frac{3}{4}*0.4=\frac{3*4+3}{4}*\frac{4}{10}=\frac{15}{4}*\frac{2}{5}=\frac{15*2}{4*5}=\frac{3*1}{2*1}=\frac{3}{2}=1.53
4
3
∗0.4=
4
3∗4+3
∗
10
4
=
4
15
∗
5
2
=
4∗5
15∗2
=
2∗1
3∗1
=
2
3
=1.5
\frac{1}{5}*4.85=\frac{1}{5}*\frac{485}{100}=\frac{1*485}{5*100}=\frac{1*97}{1*100}=\frac{97}{100}=0.97
5
1
∗4.85=
5
1
∗
100
485
=
5∗100
1∗485
=
1∗100
1∗97
=
100
97
=0.97